Emplacing New Tracing: Adding OpenTelemetry to Envoy - Ellis, Alexander. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Computer Science.; Advisor: Raja Sambasivan.; Committee: Mark Hempstead, and Fahad Dogar.; Keyword: Computer science.